Triboelectric Performance of Ionic Liquid, Synthetic, and Vegetable Oil-Based Polytetrafluoroethylene (PTFE) Greases - Nur Aisya Affrina, Mohamed Ariffin; Lee, Chiew Tin; Arunkumar, Thirugnanasambandam; Wong, King Jye; William Chong, Woei Fong (MDPI, 2024)
Within electrical contacts, poor electrical conductivity of lubricants can lead to triboelectric charging, causing electrostatic currents and thermal effects, which accelerate lubrication failure. This study aimed to address these challenges by producing and testing three greases with different base oils: ionic liquid ([Oley][Oleic]), synthetic oil (PAO4), and vegetable oil-based synthetic ester (trimethylolpropane oleate). Each grease was prepared with polytetrafluoroethylene powder as the thickener. The greases were tested using a custom-made tribometer, integrated with a grounded electrical current system, with friction tests conducted with up to a 2 A electrical current flow at a constant voltage supply of 4.5 V. Under triboelectric friction testing, [Oley][Oleic] grease outperformed a commercial perfluoropolyether grease by 27.7% in friction and 16.3% in wear. This grease also showed better performance than formulated lithium grease with extreme pressure additives. The study demonstrates that greases with low interfacial resistance can retain their lubrication capacity under triboelectric conditions. These results indicate that [Oley][Oleic] grease, with its ionic liquid base oil, offers a promising solution for applications involving electrical contacts. This study highlights the potential of using advanced base oils and thickeners to enhance the performance and sustainability of lubricants in demanding environments